(untitled) (Bangladesh Journal of Nutrition, 2015)
A prospective cohort study was undertaken to determine the optimum level of iodine in salts at household level which is best suitable to fulfill daily requirements and not excrete too much iodine in urine. A total number of 99 households of 3rd categories and 4th categories employees of Dhaka University, Bangladesh, living in university campus, were randomly divided into 3 groups. A total 778 causal urine samples from 351 individuals of the total households were collected and urinary iodine was estimated by the wet digestion method adapted by Gutekunst et.al. to determine the feeding effect of different levels of iodine in salts. The overall median urinary iodine were 202.7, 196.9 and 238.0 µg/l during baseline study and baseline consumption pattern showed that mean iodine content of salts were 41.6, 34.1 and 36.9 ppm in group-1, group-2 and group-3 respectively. The first follow-up results showed that the overall median urinary iodine were 92.9, 165.2 and 265.6 µg/l and at that time their average iodine content of the experimental salts were 17.5, 27.5 and 45 ppm in group-1, group-2 and group-3 respectively. During first follow-up the majority (72.7%) of the selected population were biochemically iodine deficient in group-1 whereas, almost all (99.1 %) were normal in group-2 and a remarkable fraction of the population (37.9%) excreted excessive urinary ’ iodine in group-3. The second follow-up findings indicates the overall median urinary iodine were 156.5, 169.3 and 180.3 µg/l in group-1, group-2 and group-3 respectively and at that time their experimental salt contained same amount of iodine (25-30 ppm). Iodine nutriture status of the study subjects during second follow-up revealed that almost all subjects (97.3%) were normal in group-!, on the other hand, biochemically deficient or excessive excretion of urinary iodine was not observed in group-2 and group-3 i.e. all of the subjects were within the normal range (UI 100-299.99 µg/l) of urinary iodine excretion.